Retail Bank Interest Rate Pass-Through : Is Chile Atypical? - Rebucci, Alessandro (IMF Working Papers; Working Paper, 2003)
This paper investigates empirically the pass-through of money market interest rates to retail banking interest rates in Chile, the United States, Canada, Australia, New Zealand, and five European countries. Overall, Chile's pass-through does not appear atypical. Based on a standard error-correction model, we find that, as in most countries considered, Chile's measured pass-through is incomplete. But Chile's pass-through is also faster than in many other countries considered and is comparable to that in the United States. While we find no significant evidence of asymmetry in Chile's pass-through across states of the interest rate or monetary policy cycle, we do find some evidence of parameter instability, around the time of the Asian and Russian crises. However, we do not find evidence that the switch to a more flexible exchange rate regime in 1999 and the "nominalization" of Chile's interest rate targets in 2001 have affected significantly the pass-through process.